The Importance Value Index of medicinal plants traditionally used by local and tribal communities of Chenab Valley of Jammu and Kashmir, India - Akhtar, Shazia; Naithani, Suman; Thapliyal, Asha; Bachheti, Archana (Ethnobotany Research and Applications, 2025)
Background: Medicinal plants constitute an integral component of the traditional healthcare system, particularly in Jammu and Kashmir. The indigenous communities of Doda Valley rely extensively on ethnomedicinal knowledge for primary healthcare. This study systematically documents and evaluates the medicinal potential species utilized in the region, providing quantitative insights into therapeutic significance and ethnobotanical relevance. Methods: A quantitative ethnobotanical assessment was conducted using standardized indices, the Importance Value Index (IVI), Percentage Respondent Knowledge Index (PRKI), Informant consensus Factor (ICF), and Fidelity level (FL) to evaluate the significance of medicinal plant species. Plant diversity was analyzed across 15 sites using a quadrat-based approach with of 10 m × 10 m (trees) 5 m × 5 m (shrubs) and 1 m × 1 m (herbs.) Species is identification, collection and enumeration following standard taxonomic protocols, ensuring methodological rigor and reproducibility. Results: A total of 21 medicinal plant species belonging to 31 medical applications. Digestive disorders showed a high Informant consensus factor (0.96), with Cannabis sativa having the highest Fidelity Level (96.7). Topical use and decoctions were common (42.8%), with 35% of remedies using whole plants. Most plants (61.9%) were sourced from natural habitats, 14.2% from cultivated areas, and 23.8% from both. Conclusions: The ethnobotanical findings reveal the substantial therapeutic potential of medicinal plants in the Doda Valley, with certain species exhibiting high fidelity in traditional medicine. Future research should prioritize the isolation, structural elucidation, and pharmacokinetic characterization of bioactive compounds to advance novel drug discovery and promote sustainable utilization. Keywords: Ethnobotany, Medicinal plants, Percent use-value, Informant consensus factor.